ABC's of cultural understanding and communication : national and international adaptations - Schmidt, Patricia Ruggiano, 1944-; Finkbeiner, Claudia (Language, literacy, and learning., 2006)
This book is a valuable one for teacher educators and teacher education programs in the United States and Europe, since it is organized around numerous data sources. It contains national and international adaptations of the ABC's of Cultural Understanding and Communication. Authors for this book represent many languages and cultures and know, first hand, the socially constructed issues related to language, culture, and ethnicity. This book promises to make a significant contribution to preparing teachers to work with families and children. It should be read by all teacher educators as well as preservice and inservice teachers. In the new millennium teachers must redefine their responsibilities to ensure that ALL children have the opportunity to succeed. ABC's of Cultural Understanding and Communication: National and International Adaptations is a perfect place to start.